Crisis management of food security scandals in China: Motivations and solutions towards purchase intention - Li, Y.; Phau, Ian; Lu, W.; Teah, Min (John Wiley & Sons, 2017)
© 2017 John Wiley & Sons, Ltd. This research employs 2 studies to investigate the changes in consumers' purchase intention after food safety scandals. The first study investigates changes in consumer behavior directly after a food scandal. The second study takes a follow-up investigation on consumer reactions to 6 hypothetical scenarios. The respondents were recruited from large universities and career training centers of Chinese corporations through a convenience sample. Six hundred forty-nine valid responses were obtained. The data were analyzed using SPSS and structural equation modelling. Consumers' purchase intention declines rapidly in the short term after a food safety scandal. The decline in purchase intention mainly depends on consumer's individual attitude and subjective norm, which are largely affected by the perceived risk, negative emotion, trust in the enterprise, self-esteem, present temporal orientation, and hedonic consumption with food. Furthermore, government regulation, corporate crisis management, and media coverage affect the consumers' purchase intention.